Where the ground meets the sky - Davies, Jacqueline (Marshall Cavendish, 2002)
During World War II, a twelve-year-old girl is uprooted from her quiet, East coast life and moved to a secluded army post in the New Mexico desert where her father and other scientists are working on a top secret project.